1996
DOI: 10.1093/humrep/11.3.486
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating ovarian reserve: follicle stimulating hormone and oestradiol variability during cycle days 2-5

Abstract: A prospective measurement of follicle stimulating hormone (FSH) and oestradiol between cycle days 2 and 5 was conducted to investigate the intra- and inter-cycle variability in a healthy population of women with regular menstrual intervals. Daily serum samples were obtained from 44 women for a total of 66 cycles on cycle days 2, 3, 4 and 5. FSH concentrations were consistent on all cycle days measured. Oestradiol concentrations on cycle day 2 were not different from cycle day 3, but concentrations on cycle day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1
4

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 16 publications
1
24
1
4
Order By: Relevance
“…Serum FSH concentrations are stable across d 2-5 in normally cycling young women (30,31), but it was not clear whether they remained so in older women (32,33). Our data demonstrate that early follicular FSH levels are stable in older cycling women.…”
Section: Discussionmentioning
confidence: 59%
“…Serum FSH concentrations are stable across d 2-5 in normally cycling young women (30,31), but it was not clear whether they remained so in older women (32,33). Our data demonstrate that early follicular FSH levels are stable in older cycling women.…”
Section: Discussionmentioning
confidence: 59%
“…AMH, which is a product of primary, pre-antral and early antral follicles, is expressed by granulosa cells and is detectable in some primary and secondary follicles (2-6 granulosa cell layers) and in essentially all pre-antral and small (<6 mm) antral follicles [30,31]. Other researchers have used the fractionator/optical disector technique to estimate the human numbers of primordial follicles (oocyte pools) and determined that the age-adjusted correlation between serum AMH and the oocyte pool is 0.48, which supports the view that AMH reflects the size of the oocyte pool [14]. It has been reported that in 4-to 18-month-old C57BL/6j mice, the serum AMH levels decline with increasing age and directly correlate with declining numbers of growing and primordial follicles [32].…”
Section: Disscussionmentioning
confidence: 67%
“…While it is clear that maternal ageing has multifaceted detrimental effects on oocyte development, the association between oocyte pool size and aneuploidy rates of ovulated oocytes has not been directly examined. It has been reported that oocyte quality decreases in parallel with the progressive loss of follicle number [13][14][15]. However, according to our knowledge, this is the first study that provides direct evidence for how ovarian follicle number is related to aneuploidy rates in young and aged mice by using whole ovarian follicle counting.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 80%
“…Afterwards, progesterone and estrogen concentration rapidly decline which leads to the bleeding. Responding to the low levels of estrogen, the hypothalamus again causes release of FSH and the cycle begins again [16]. One method of examining the validity of fertility monitors using saliva is to compare them with established markers of ovulation, such as LH in urine.…”
Section: Introductionmentioning
confidence: 99%